2012
DOI: 10.2220/biomedres.33.89
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation therapy on upper extremity functional recovery and cerebral cortical changes in patients with chronic hemiplegia

Abstract: Hemiplegia is a common sequel of stroke and assisted living care is needed in many cases. The purpose of this study was to evaluate the effect of using surface electrode stimulation device in rehabilitation, in terms of functional improvement in upper limb and the changes in brain activation related to central nervous system reconstruction. Five patients with chronic hemiplegia received electrical stimulation therapy using the orthosis-type surface electrode stimulation device for 12 weeks. Training time was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…On the one hand, some studies found either an increase of fMRI BOLD signal in the contralesional postcentral gyrus [9,34] as a correlate of enhanced cortical activation or a decrease of activation in the ipsilesional hemisphere correlated to reduced cortical activation [31]. On the other hand, other research groups propose that FES, accompanied by improvement of motor function, leads to less diffuse activity in the sensorimotor cortex (SMC), shifting to focused activity in the ipsilesional SMC [32,33]. Likewise, a recent study investigating changes of cortical brain perfusion using near-infrared spectroscopy (NIRS) during and after therapeutic FES intervention found a redistribution towards the ipsilesional SMC in patients with improved functional motor control following FES [30].…”
Section: Reviewmentioning
confidence: 99%
“…On the one hand, some studies found either an increase of fMRI BOLD signal in the contralesional postcentral gyrus [9,34] as a correlate of enhanced cortical activation or a decrease of activation in the ipsilesional hemisphere correlated to reduced cortical activation [31]. On the other hand, other research groups propose that FES, accompanied by improvement of motor function, leads to less diffuse activity in the sensorimotor cortex (SMC), shifting to focused activity in the ipsilesional SMC [32,33]. Likewise, a recent study investigating changes of cortical brain perfusion using near-infrared spectroscopy (NIRS) during and after therapeutic FES intervention found a redistribution towards the ipsilesional SMC in patients with improved functional motor control following FES [30].…”
Section: Reviewmentioning
confidence: 99%
“…In fact, this kind of study design (focusing on chronic patients with stabilized hemiplegia and without control subjects) is often taken in the pilot studies where the effect of new rehabilitation therapy for the hemiplegia was investigated, e.g., to evaluate the effects of electrical stimulation on the upper limb function and pain [42][43][44][45] and the effects of robotic therapy on the upper extremity functions [46,47]. Negligible effects of the natural recovery or the conventional therapy on the improvement of the shoulder motor function is also supported by the fact that the functional (FMA score) improvement is exclusively demonstrated for the shoulder-related items (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Neural plasticity, which is presumed to play a major role in motor recovery, can be modulated by various exogenous methods, including electrical stimulation [5,6]. Epidural cortical stimulation (ECS), a therapeutic that exposes dura mater by craniotomy for electrical stimulation of the cortex, has demonstrated significant improvements in motor function in animal models of stroke and as an adjunctive treatment in limb motor function rehabilitation of stroke patients with hemiparesis by modulating neuronal plasticity [4,7,8,9,10,11,12]. In addition, approximately one-third of stroke patients present with the devastating consequences of aphasia, the inability to speak [13].…”
Section: Introductionmentioning
confidence: 99%